Investigation of the effect of book reading activity on attention level and reaction time in student athletes - Nuray Satilmis; Pelin Avci; Gokmen Kilicarslan; Isik Bayraktar; Akan Bayrakdar (ROL Spor Bilimleri Dergisi)
The aim of this study is to investigate the effect of regular book reading activity on attention level and reaction time in student athletes. The study group consists of 33 student athletes, 17 individuals in control group and 16 individuals in experiment group, doing individual or team sports. Experiment group read books for a period of 40 minutes, three times a week. In addition to personal information form, “Visual Attention Test” is applied to volunteers. The data of the research were evaluated in the SPSS program. Differences were observed in reaction time of students who regularly read books and not (p<0.05). While no difference was observed in accuracy ratio of student athletes who do not read books, differences were found in student athletes who read (p<0.05). While no differences were observed on accuracy ratio of student athletes doing individual sports who do not read books regularly, differences were determined on accuracy ratio of student athletes doing team sports. There were differences on accuracy ratio of student athletes doing individual sports or team sports and who read books regularly. In conclusion, it is determined that students doing individual sports or team sports who read books regularly have better attention levels compared to those who do not read books.